2021
DOI: 10.3390/antiox10010114
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Urinary Metal and Metalloid Concentrations in Association with Oxidative Stress Biomarkers

Abstract: Metal exposure has been associated with a wide range of adverse birth outcomes and oxidative stress is a leading hypothesis of the mechanism of action of metal toxicity. We assessed the relationship between maternal exposure to essential and non-essential metals and metalloids in pregnancy and oxidative stress markers, and sought to identify windows of vulnerability and effect modification by fetal sex. In our analysis of 215 women from the PROTECT birth cohort study, we measured 14 essential and non-essential… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 93 publications
(71 reference statements)
0
3
0
Order By: Relevance
“…Oxidative stress influences many adverse birth outcomes, including preeclampsia, premature delivery, and intrauterine growth restriction [ 10 ]. Since most trace metals, including essential trace metals, are redox-active, they have the potential to boost ROS generation [ 11 ]. Furthermore, due to differences in various metabolic pathways between the fetus and the mother, the fetus is highly sensitive to trace metals, even at low levels of exposure that do not affect the mother [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Oxidative stress influences many adverse birth outcomes, including preeclampsia, premature delivery, and intrauterine growth restriction [ 10 ]. Since most trace metals, including essential trace metals, are redox-active, they have the potential to boost ROS generation [ 11 ]. Furthermore, due to differences in various metabolic pathways between the fetus and the mother, the fetus is highly sensitive to trace metals, even at low levels of exposure that do not affect the mother [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…41 Research evidence suggests that it is a promising index for inflammatory disorders promoted by cyclooxygenase. 42,43 The researcher found lower in urinary 8-iso-PGF 2α content in RA patients than that of a normal individual, which was significant.…”
Section: -Isoprostanementioning
confidence: 96%
“…Oxidative stress, defined as the imbalance between the reactive oxygen species (ROS) and antioxidant systems in the body, has been proposed as a key mechanism linking chemical and nonchemical stress exposures to cognitive development. For example, numerous epidemiologic studies have shown that prenatal exposure to environmental chemicals, including phthalates, metals, and per‐ and polyfluoroalkyl substances, are associated with an increase in multiple oxidative stress biomarkers during pregnancy (Ashrap et al., 2021; Cathey et al., 2021; Ferguson et al., 2015; Taibl et al., 2022). Experiences of stressful life events and socioeconomic deprivation have also been linked to elevated oxidative stress biomarkers in pregnant and nonpregnant populations (Eick et al., 2018; Schiavone et al., 2013).…”
Section: Introductionmentioning
confidence: 99%